Understanding the good and poor cell targeting activity of gold nanostructures functionalized with molecular units for the epidermal growth factor receptor. Issue 5 (10th April 2019) - Mazzuca, Claudia; Di Napoli, Benedetta; Biscaglia, Francesca; Ripani, Giorgio; Rajendran, Senthilkumar; Braga, Andrea; Benna, Clara; Mocellin, Simone; Gobbo, Marina; Meneghetti, Moreno; Palleschi, Antonio
Abstract : The key role of polyethylene glycol is demonstrated. Abstract : Nanostructures can strongly interact with cells or other biological structures; furthermore when they are functionalized with targeting units, they are of great interest for a variety of applications in the biotechnology field like those for efficient imaging, diagnosis and therapy and in particular for cancer theranostics. Obtaining targeting with good specificity and sensitivity is a key necessity, which, however, is affected by the complexity of the interactions between the nanostructures and the biological components. In this work we report the study of specificity and sensitivity of gold nanoparticles functionalized with the peptide GE11 for the targeting of the epidermal growth factor receptor, expressed on many cells and, in particular, on many types of cancer cells. We show how a combination of spectroscopic measurements and molecular dynamics simulations allows the comprehension of the targeting activity of peptides linked to the surface of gold nanostructures and how the targeting is tuned by the presence of polyethylene glycol chains.